In Situ Analysis of Heliospheric Current Sheet Propagation. Issue 10 (13th October 2017) - Peng, Jun; Liu, Yong C.‐M.; Huang, Jia; Li, Hui; Klecker, Berndt; Galvin, Antoinette B.; Simunac, Kristin; Farrugia, Charles; Jian, L. K.; Liu, Yang; Zhang, Jie
Abstract: The heliospheric current sheet (HCS) is an important structure not only for understanding the physics of interplanetary space but also for space weather prediction. We investigate the differences of the HCS arrival time between three spacecraft separated in heliolongitude, heliolatitude and radial distance from the Sun (STEREO A, STEREO B, and ACE) to understand the key factors controlling the HCS propagation. By assuming that the source of the solar wind does not evolve except for the effects of solar rotation, we first test the first‐order approach method (ignoring latitudinal differences), using STEREO observation during the year 2007, when the Sun was quiet and the two STEREO spacecraft were separated in heliolongitude by less than 44°. The first‐order approach method matches well with observations for many events except for those events when the HCS has a small inclination angle to the ecliptic plane. The latitudinal effect is suggested to account for such discrepancies. The predictions are not improved much by considering the HCS inclination angle obtained from the potential field source surface (PFSS) model. However, the predictions match well with the observations when the HCS inclination angle at 1 AU is obtained from the time differences of HCS arrival times between the STEREO B and ACE spacecraft. An improved model of calculating the inclination of the heliospheric current sheet other than PFSS is needed. Key Points: Latitudinal effect is important for the heliospheric current sheet (HCS) propagation Latitudinal effect is significant when a HCS has a small inclination angle The HCS inclination angle is better determined using the observation at 1 AU